Antibiotic overuse, poor antimicrobial stewardship, and low specificity of syndromic case management in a cross section of men with urethral discharge syndrome in Kampala, Uganda - Hamill, Matthew M.; Onzia, Annet; Rosalind, M. Parkes-Ratanshi; Kyambadde, Peter; Mande, Emmanuel; Nakate, Vivian; Johan, H. Melendez; Ethan, Gough; Manabe, Yukari C. (PLoS ONE, 2024)
Objective High prevalence of sexually transmitted infections (STIs) combined with poor antimicrobial stewardship are drivers of STI antimicrobial resistance (AMR) especially in resource-limited settings where syndromic case management (SCM) is the norm. We characterized patterns of antibiotic use prior to clinic attendance and study enrollment in Ugandan men with urethral discharge syndrome (UDS), evaluated in-clinic prescribing, and the performance characteristics of SCM. Methods Participants were recruited from government clinics participating in an existing gonococcal surveillance program in Kampala, Uganda. Questionnaires including antimicrobial use prior to attendance, prior episodes of UDS, penile swabs, and blood samples were collected. Bivariable and multivariable logistic regression models were used to estimate odds ratios (OR) for preselected factors likely to be associated with antibiotic use. In-clinic antibiotic treatment data were extracted from clinical notes, and the performance of SCM against laboratory-based STI diagnoses was evaluated. Findings Between October 2019 and November 2020, 100(40%) of 250 men with UDS reported taking antibiotics in the 14days prior to attending the clinic. Of these 210(84%) had at least one curable STI and 20% had a reactive point-of-care HIV test. Multivariable analysis demonstrated significant associations between recent antimicrobial use and duration of UDS symptoms <6 days (OR 2.98(95%CI 1.07,8.36), p = 0.038), and sex with women only (OR 0.08(95%CI 0.01,0.82),p = 0.038). The sensitivity of SCM ranged from 80.0% to 94.4%; specificity was low between 5.6% and 33.1%. The positive predictive value of SCM ranged from 2.4(95%CI 0.7,6.0) for trichomoniasis to 63.4(95%CI 56.5,69.9) for gonorrhea. Conclusion Pre-enrollment antibiotic use was common in this population at high risk of STI and HIV. Combined with the poor specificity of SCM for male UDS, extensive antibiotic use is a likely driver of STI-AMR in Ugandan men. Interventions to improve antimicrobial stewardship and deliver affordable diagnostics to augment SCM and decrease overtreatment of STI syndromes are required.